2009
DOI: 10.1111/j.1708-8305.2008.00283.x
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes, and Practices of French Travelers from Marseille Regarding Rabies Risk and Prevention

Abstract: The KAP of French travelers with regard to travel-associated rabies risk need to be improved, particularly regarding the prevention of animal bites, postbite measures, and their urgency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 16 publications
3
44
0
1
Order By: Relevance
“…This finding is similar to those of previous studies that found that most travelers are not vaccinated for rabies before travel (Altmann et al 2009, Gautret et al 2008, Piyaphanee et al 2010. Specifically, 60% of GTEN travelers visiting a single strong- a Travelers could choose more than one purpose for travel; therefore, the total purposes of travel exceed the number of vaccinated travelers (n = 406) and unvaccinated travelers (n = 12,603).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…This finding is similar to those of previous studies that found that most travelers are not vaccinated for rabies before travel (Altmann et al 2009, Gautret et al 2008, Piyaphanee et al 2010. Specifically, 60% of GTEN travelers visiting a single strong- a Travelers could choose more than one purpose for travel; therefore, the total purposes of travel exceed the number of vaccinated travelers (n = 406) and unvaccinated travelers (n = 12,603).…”
Section: Discussionsupporting
confidence: 80%
“…Other studies have found that travelers refused vaccination because of high cost, low perception of benefit, concern for an adverse reaction, and belief that vaccination was not necessary (Altmann et al 2009, Piyaphanee et al 2010. In fact, the average wholesale price of an individual rabies vaccine dose for pre-exposure vaccination can range from $194 to $240 (Anonymous 2008).…”
Section: Dolan Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are not unique to our backpacker group, and have been confirmed in several other studies. 13,14 Our subgroup analysis of the group who had visited a travel clinic, and those who had not, found that significantly more members of the travel clinic group had received information and vaccinations against rabies than the control group. Unfortunately, even in the travel clinic group, the serious misunderstandings mentioned previously still existed in comparable percentages to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…These studies demonstrated a high level of people's awareness regarding rabies. A few other studies have also reported about knowledge and perception of rabies risk among travelers travelling in rabies-endemic countries (Altmann et al, 2009;Piyaphanee et al, 2010). However, these studies have also found that people apply chilli and turmeric powder, lime, kerosene oil, herbal paste or salt on the dog bite wound, or perform folk remedies at home rather than seeking conventional treatment from health facilities (Agarvval and Rabies is endemic in south Bhutan (an area that borders India) and results in sporadic human deaths (approximately 0.28 deaths per100000 population per year) following rabid dog bites (Tenzin.…”
Section: Introductionmentioning
confidence: 99%